Prague, the city of traditions and shopping centres. A case study - Sikos T, Tamás (Hungarian Geographical Bulletin, 2013)
Prague is one of the most beautiful cities in Europe. In this metropolis of history and traditions shopping centres have also appeared and they have made remarkable impact on the city’s commercial structure. The impact of shopping centres on trade and shoppers in Prague was examined in details. In our research we aimed to describe the evaluation and the changes in buying habits in the city. We gave a brief historical review of the opening of the centres and their locations in the Czech capital were also examined. Our examination was based on primary and secondary researches. In our primary research we relied on a questionnaire in which 501 customers were inquired about the aim of their shopping. Data collection took place in Palladium shopping center in the Old Town of Prague and in Arkády Pankrác shopping center in the suburban area. The number of respondents in Palladium was 252, while in Arkády Pankrác it was 249.